Evaluation Guidelines: Applying the QoR4D Frame of Reference to Process and Performance Evaluations, Workshop Report, February 2023 - CGIAR Independent Advisory and Evaluation Service (2023)
CGIAR’s Independent Advisory and Evaluation Service (IAES) provides operational support as the Secretariat for the Independent Science for Development Council (ISDC) and the Standing Panel on Impact Assessment (SPIA). IAES implements CGIAR’s multi-year, independent evaluation plan, as approved by the System Council. The IAES multi-year workplan authorizes the IAES Evaluation Function’s continued role in supporting evaluation standards, guidance, and capacity within CGIAR. Furthermore, as custodian of the evaluation policy, it is tasked in the IAES terms of reference with ensuring excellence across the CGIAR-wide evaluation practice and with operationalizing the CGIAR Evaluation Policy & Framework (2022).